Manufacturing Populism: Digitally Amplified Vernacular Authority - Howard, Robert Glenn (2022)
This article shows that digital technologies can play an outsized role in populist discourse because the imagined “voice of the people” gains its authority through the appearance of continuities and consistencies across many iterative communication events. Those iterations create an observable aggregate volition which is the basis of vernacular authority. Digital technologies give institutions the ability to generate those iterative communications quickly. Through example analyses, I show three different ways that institutional actors deployed digital technologies to promote their populist political agendas by manufacturing “the will of the people.” Each of these examples suggests that digital technologies hybridize communication in ways that suggest the elite are always already part of “the people.”